2013
DOI: 10.15517/rbt.v61i1.10886
|View full text |Cite
|
Sign up to set email alerts
|

Genealogical approaches to the temporal origins of the Central American gap: Speciation and divergence in Pacific <i>Chthamalus</i> (Sessilia: Chthamalidae)

Abstract: Abstract:A large section of the tropical Eastern Pacific coastline is nearly devoid of reef or consolidated habitat, and is known as the Central American Gap as it is associated with a biogeographic transition in fish and invertebrate species. We analyze phylogeographic data for intertidal barnacles (Chthamalus) to identify relevant temporal patterns that describe the origins of this biogeographic transition (the Mexican-Panamic Transition Zone). These contrasts of populations on either side of the transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
(57 reference statements)
0
13
0
Order By: Relevance
“…Hellberg () showed that the range overlap among recently diverged lineages of the gastropod Tegula followed isolation between wave‐exposed and wave‐sheltered environments, a pattern that is also found in some tropical eastern Pacific barnacles (Meyers et al. ). Abundant evidence shows that “ecological” speciation or divergence is possible in marine systems (Sanford et al.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Hellberg () showed that the range overlap among recently diverged lineages of the gastropod Tegula followed isolation between wave‐exposed and wave‐sheltered environments, a pattern that is also found in some tropical eastern Pacific barnacles (Meyers et al. ). Abundant evidence shows that “ecological” speciation or divergence is possible in marine systems (Sanford et al.…”
Section: Introductionmentioning
confidence: 85%
“…For example, complex patterns may develop when distinct coastal environments promote the divergence of populations. Hellberg (1998) showed that the range overlap among recently diverged lineages of the gastropod Tegula followed isolation between wave-exposed and wave-sheltered environments, a pattern that is also found in some tropical eastern Pacific barnacles (Meyers et al 2013). Abundant evidence shows that "ecological" speciation or divergence is possible in marine systems (Sanford et al 2003;Schmidt et al 2008), so the interaction between dispersal and fitness is an important component for describing the origins of marine biodiversity.…”
Section: Introductionmentioning
confidence: 94%
“…This suggests that many TEP species are capable of dispersing across the CAG and may have relatively high dispersal potential (Robertson & Cramer 2009). But in order to more fully assess the degree to which the CAG and other tropical habitat gaps may limit dispersal, population genetic studies, coupled with field surveys of abundance, distribution, larval dispersal potential (plus its interaction with temperature; O'Connor et al 2007) and recruitment success for tropical species are needed (Meyers et al 2013;Marchant et al 2015). Nevertheless, the total range extents of tropical/subtropical species tend to be larger than extratropical species (measured as total km of coastline between species' range limits) partly because many TEP species appear capable of dispersing across large habitat gaps such as the CAG.…”
Section: Predictors Of Biogeographic Structure and Richnessmentioning
confidence: 99%
“…A remaining question is why particular environmental boundaries appear to influence the connectivity among locations for some species but not others. As with the comparison between N. scabrosus, which exhibits strong population structure along the Chilean coast (Zakas et al 2009;Laughlin et al 2012), and J. cirratus, which does not, we can also consider the structure of Balanus glandula (Sotka et al 2004) (not a chthamalid barnacle, however) against the lack of structure in the codistributed Chthamalus dalli (Wares and Castañeda 2005), the structure in C. montagui across a broad geographic range (Dando and Southward 1981) and lack of structure across a similar range in C. stellatus (O'Riordan et al 2010), along with other examples (Zardus and Hadfield 2005;Tsang et al 2008;Wares et al 2009;Meyers et al 2013). Are the differences in structure based on larval behavior or developmental time (Burton and Feldman 1982)?…”
Section: Discussionmentioning
confidence: 99%
“…Here, we add sequences from subsequent samples within this range, as well as samples from the edges of the distribution (Häussermann and Försterra 2009), now spanning close to 3000km of the species' range, to explore more fully the potential for spatial diversity in intertidal taxa from this coast (see Figure 1). As chthamalid barnacles have a propensity to harbor cryptic genetic diversity (Dando and Southward 1981;Zardus and Hadfield 2005;Tsang et al 2008;Wares et al 2009;Meyers et al 2013), we specifically look for any phylogeographic structure that may add to our understanding of coastal biodiversity in Chile.…”
Section: Introductionmentioning
confidence: 99%